Profile of HIV/AIDS Patients Coinfected with Tuberculosis in Bumi Wonorejo Health Centre and Santo Rafael Clinic Nabire, Papua - Kridaningsih, Tri Nury; Widiyanti, Mirna; Adiningsih, Setyo; Hutapea, Hotma Martogi Lorensi; Fitriana, Eva; Natalia, Evi Iriani (Fakultas Kedokteran Universitas Brawijaya, 2021)
HIV-TB co-infection still becomes a health problem in Indonesia, including in Nabire district, Papua province, which has the highest number of cases. HIV and TB infections are closely related and affect the epidemiology of one another. This study aims to determine the profile description of HIV-TB co-infected patients in Nabire. This research is a descriptive study with a cross-sectional design on 90 people with HIV/AIDS selected consecutively. Data were analyzed univariately and presented in the form of a frequency distribution table. The results showed that of 55 HIV/AIDS co-infected TB patients, almost all (90.9%) were Papuan ethnic, 70.9% were female and aged 30 to 49 years (50.9%) with a mean of 31.309.36 years. The majority of HIV-TB co-infected patients were married (63.6%), holding secondary education (58.2%), working (67.3%), engaging in sexual activity after 17 years of age, only having one sexual partner, and did not use drugs or obtain blood transfusions. The clinical profile of HIV-TB patients showed that 67.3% of the patients were with baseline CD4 count â‰¤350 cells/mm3, 64.8% had CD4 count at the time of study >350 cells/mm3, and viral load values fewer than 5000 copies/ml (87.3%). The therapy most widely received for patients with HIV-TB coinfection was the combination of ARV 3TC+EFV+TDF (76.4%). The most common clinical symptoms of HIV/AIDS patients were weight loss (56.4%), cough (40%), recurrent oral thrush (36.4%), chickenpox (32.7%), and tuberculosis lymph nodes (18.2%).